Lost in the detail: Prosecutors' perceptions of the utility of video recorded police interviews as rape complainant evidence - Westera, Nina J. (The Australian and New Zealand journal of criminology, 2017)
This study explored the perceptions of ten Crown Prosecutors about the utility of police interviews as video evidence-in-chief for adult sexual assault complainants to determine how to improve these interviews. A themed analysis of prosecutors' responses indicated three major concerns about these interviews: the interviewer using wordy instructions, the lack of chronology and logical structure, and the relentless pursuit of unnecessary detail. These findings suggest that prosecutors' concerns are primarily due to police using cognitive interview methods that attempt to enhance the amount of detail recalled by a complainant. The authors discuss why generating large amounts of detail may be problematic in interviews with sexual assault complainants and provide recommendations for how police can adapt interview practices to better meet evidential needs.